2022
DOI: 10.3389/fvets.2022.893342
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Oral Fecal Microbiota Transplantation in a Dog Suffering From Relapsing Chronic Diarrhea—Clinical Outcome and Follow-Up

Abstract: The present case report describes the effects of orally administered fecal microbiota transplantation (FMT) (frozen capsules) in a dog suffering from relapsing chronic diarrhea, needing a continuous low prednisolone dose to maintain the condition under acceptable control. Through FMT, we aimed at evaluating the possibility of improving the clinical score and/or reducing/suspending steroid administration. During a first period of strict monitoring (21 days), the canine inflammatory bowel disease activity index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is supported by studies showing that dogs with chronic diarrhoea and IBD have markedly different intestinal bacteria and gut metabolite pro les compared with healthy dogs [12]. In recent years, faecal transplantation has gained attention as a potential new treatment modality for human IBD, and several reports have con rmed its e cacy in dogs as well [13][14][15]. These reports suggest that the gut microbiota and its metabolites play a key role in the onset and maintenance of CE and its associated symptoms; however, it is not clear which factors are responsible.…”
Section: Introductionmentioning
confidence: 88%
“…This is supported by studies showing that dogs with chronic diarrhoea and IBD have markedly different intestinal bacteria and gut metabolite pro les compared with healthy dogs [12]. In recent years, faecal transplantation has gained attention as a potential new treatment modality for human IBD, and several reports have con rmed its e cacy in dogs as well [13][14][15]. These reports suggest that the gut microbiota and its metabolites play a key role in the onset and maintenance of CE and its associated symptoms; however, it is not clear which factors are responsible.…”
Section: Introductionmentioning
confidence: 88%
“…Available data suggest beneficial effects of FMT in patients with mild to moderate ulcerative colitis (UC), but there is insufficient evidence to recommend this therapeutic modality in routine clinical practice, and its use is currently limited to a research setting [ 95 ]. In dogs, only one RCT, one prospective study and six case reports/series on the use of FMT in dogs with CIEs/IBD have been published to date [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. In the RCT, dogs with IBD were given either a FMT or a sterile saline enema as a placebo in addition to prednisolone and a hydrolyzed diet [ 102 ].…”
Section: Limitations and Reconsideration Of The Current Classificationmentioning
confidence: 99%
“…[18][19][20][21] In veterinary medicine, FMT has been utilized for IBD, acute diarrhea, chronic enteropathy, and parvoviral infections. [22][23][24][25][26][27][28] Given the relationship between the gut microbiome and the host's immune system, FMT can lead to changes in their complex signaling and interactions. Human-and mouse-based FMT studies have shown changes affecting the peripheral immune system, such as a decrease in serum pro-inflammatory cytokines, and an increase in anti-inflammatory bacteria and T regulatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Possible benefits may be seen in inflammatory bowel disease (IBD), irritable bowel syndrome, and hepatic encephalopathy 18‐21 . In veterinary medicine, FMT has been utilized for IBD, acute diarrhea, chronic enteropathy, and parvoviral infections 22‐28 …”
Section: Introductionmentioning
confidence: 99%